Anchoring among German financial analysts: An empirical and background analysis - Tomfort, Andre; Wiegand, Paulina (Journal of Economics and Behavioral Studies, 2020)
The paper investigates whether financial analysts in Germany were subject to cognitive and emotional constraints. The focus was on the heuristic of anchoring. An evaluation based on 224 individual forecasts for seven DAX-listed companies for the period from 2011 to 2018 with respect to the earnings per share of the current business year was done. Three issues were analysed in particular: Whether anchoring was found at all, to what extent anchoring has led to a deterioration of the forecast quality and if the effect of anchoring was still measurable shortly before the incurred earnings had been announced. For the assessment of the data, descriptive statistical measures, and tests such as the non-parametric Wilcoxon rank-sum test or the parametric t-test were used. For the German capital market there are currently very few empirical behavioural studies dealing with the forecast quality of financial analysts. This study is aiming to close this gap by investigating to what extent behavioural aspects have led to a significant deterioration in the forecast quality of financial analysts for the German stock market. The quality and reliability of analysts’ forecasts is of high relevance to the capital market, since the assessments of financial analysts are used as a basis for investment decisions by private and institutional investors and are thus essential for a high degree of efficiency in the allocation of capital in a financial system.